Analisis Kerusakan Lingkungan Fisik Akibat Penambangan Pasir Dan Batu Di Kabupaten Sleman Daerah Istimewa Yogyakarta - Agung Dwi Sutrisno (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2016)
Sand and stone mining Sleman increasingly prevalent after the eruption of Mount Merapi in 2010. Theaim of this study is 1) assess the factors causing physical damage caused by mining of sand andstones in Sleman; 2) analyze the extent of the damage. This research approach uses direct fieldobservation method and survey. Data taken at 16 sites in four districts, each taken two samples of themine site that is in the moor and two samples of the mine site is located on a river. Quantitativeanalysis is done by means of weighting and scoring and qualitatively. Each parameter is weighted inaccordance with the standards set by the environmental damage in the DIY Governor Decree No. 63of 2003. The factors known to cause damage through interviews and questionnaires administration.As a result, the damage caused by mining in the area were severely damaged moor categorized. Asfor mining on the river slightly damaged. Factors that influence the damage is lack of socialization.